nip, a Symbiotic Medicago truncatula Mutant That Forms Root Nodules with Aberrant Infection Threads and Plant Defense-Like Response - Veereshlingam, Harita (American Society of Plant Biologists, 2004)
To investigate the legume-Rhizobium symbiosis, we isolated and studied a novel symbiotic mutant of the model legume Medicago truncatula, designated nip (numerous infections and polyphenolics). When grown on nitrogen-free media in the presence of the compatible bacterium Sinorhizobium meliloti, the nip mutant showed nitrogen deficiency symptoms. The mutant failed to form pink nitrogen-fixing nodules that occur in the wild-type symbiosis, but instead developed small bump-like nodules on its roots that were blocked at an early stage of development. Examination of the nip nodules by light microscopy after staining with X-Gal for S. meliloti expressing a constitutive GUS gene, by confocal microscopy following staining with SYTO-13, and by electron microscopy revealed that nip initiated symbiotic interactions and formed nodule primordia and infection threads. The infection threads in nip proliferated abnormally and very rarely deposited rhizobia into plant host cells; rhizobia failed to differentiate further in these cases. nip nodules contained autofluorescent cells and accumulated a brown pigment. Histochemical staining of nip nodules revealed this pigment to be polyphenolic accumulation. RNA blot analyses demonstrated that nip nodules expressed only a subset of genes associated with nodule organogenesis, as well as elevated expression of a host defense-associated phenylalanine ammonia lyase gene. nip plants were observed to have abnormal lateral roots. nip plant root growth and nodulation responded normally to ethylene inhibitors and precursors. Allelism tests showed that nip complements 14 other M. truncatula nodulation mutants but not latd, a mutant with a more severe nodulation phenotype as well as primary and lateral root defects. Thus, the nip mutant defines a new locus, NIP, required for appropriate infection thread development during invasion of the nascent nodule by rhizobia, normal lateral root elongation, and normal regulation of host defense-like responses during symbiotic interactions.